O doente de hanseníase em Campinas: uma perspectiva antropológica People with leprosy in Campinas, Brazil: an anthropological perspective - Marcos S. Queiroz; Maria Angélica P. Carrasco (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1995)
Este artigo estuda a experiência de vida de doentes e comunicantes de hanseníase em Campinas, Brasil, a partir da análise de suas representações sobre saúde, doença e terapêutica. Trata-se de captar no interior das condições de vida e de trabalho destes indivíduos as estratégias que permitam adaptação ao meio social e familiar, subsistência e convivência com a doença. Atenção especial é dada à maneira pela qual estes indivíduos enfrentam o problema de manutenção e recuperação da saúde, assim como avaliam os serviços e as práticas oficiais e não-oficiais de saúde. This article studies the life experiences of people with leprosy and their intra-domiciliary families in Campinas, Brazil, based on an analysis of their representations concerning health, disease, and treatment. Taking their living and working conditions as the background, the study sheds light on the strategies that allow them to adapt to social and family life, to obtain a livelihood, and to establish familiarity with the disease process. The article focuses particularly on the way such individuals deal with the problems of regaining their health, in addition to evaluating governmental and nongovernmental health services.